Six-minute walk test in burned subjects: Applicability, reproducibility and performance at hospital discharge - Kakitsuka, Emely Emi; Morita, Andrea Akemi; Itakussu, Edna Yukimi; Kuwahara, Reinaldo Minoru; Anami, Elza Hiromi Tokushima; Pitta, Fabio; Hernandes, Nidia Aparecida (Burns, 2020)
•The 6MWT is applicable and well tolerated by burn patients at hospital discharge.•Most burn individuals increased the walked distance when two 6MWT were performed.•Burn patients, specially those with lower limb injury, had limited exercise capacity. Despite its clinical relevance in several populations, there is no evidence on applicability of the 6-min walk test (6MWT) in burned subjects. To verify the applicability and reproducibility of the 6MWT in burned individuals and to analyze patients’ performance in this test at hospital discharge. In a cross-sectional study, burned individuals performed two 6MWT at hospital discharge, according to international standardization. In addition to walked distance, physiological and symptomatic variables were collected. Clinical history and demographic data were also recorded. One hundred individuals were evaluated (70 men, 10 [6–18]% total body surface area burned). There was excellent agreement between the two 6MWT (ICC = 0.97). However, 73% of subjects increased the walked distance in the second test (23 [−9–47]m or 5 [−2–10]%; P = 0.001). Considering the best 6MWT, the walked distance was 488 [396–718]m (80 [65–92]%pred), and 51% of the individuals had limited functional exercise capacity. Additionally, participants without lower limb involvement presented better 6MWT than others (P < 0.0001). The 6MWT was applicable, well tolerated and reproducible at hospital discharge in burned individuals. However, there was considerable learning effect between the first and second test. Finally, the reduced exercise capacity observed reinforces need for early rehabilitation in this population.